2021
DOI: 10.3390/jcm10245891
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyzine Use and Mortality in Patients Hospitalized for COVID-19: A Multicenter Observational Study

Abstract: (1) Background: Based on its antiviral activity, anti-inflammatory properties, and functional inhibition effects on the acid sphingomyelinase/ceramide system (FIASMA), we sought to examine the potential usefulness of the H1 antihistamine hydroxyzine in patients hospitalized for COVID-19. (2) Methods: In a multicenter observational study, we included 15,103 adults hospitalized for COVID-19, of which 164 (1.1%) received hydroxyzine within the first 48 h of hospitalization, administered orally at a median daily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
(95 reference statements)
4
12
0
Order By: Relevance
“…We found that FIASMA psychotropic medication use was significantly and substantially associated with reduced risk of intubation or death among patients with psychiatric disorders hospitalized for severe COVID-19, and that this association was not specific to one FIASMA psychotropic class or medication in this population. These findings are in line with prior preclinical [8,12,[51][52][53][54], observational [21][22][23][24][55][56][57], and clinical [27][28][29][30] evidence that FIASMA antidepressant medications may substantially prevent cells from being infected with SARS-CoV-2 in vitro [8,12], and that FIASMA antidepressants and potentially the FIASMA anti-histamine hydroxyzine at their usual respective antidepressant and antihistaminic doses, may reduce mortality among patients with COVID-19.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found that FIASMA psychotropic medication use was significantly and substantially associated with reduced risk of intubation or death among patients with psychiatric disorders hospitalized for severe COVID-19, and that this association was not specific to one FIASMA psychotropic class or medication in this population. These findings are in line with prior preclinical [8,12,[51][52][53][54], observational [21][22][23][24][55][56][57], and clinical [27][28][29][30] evidence that FIASMA antidepressant medications may substantially prevent cells from being infected with SARS-CoV-2 in vitro [8,12], and that FIASMA antidepressants and potentially the FIASMA anti-histamine hydroxyzine at their usual respective antidepressant and antihistaminic doses, may reduce mortality among patients with COVID-19.…”
Section: Discussionsupporting
confidence: 84%
“…A retrospective observational study also established a similar association between chronic administration of a FIASMA medication and diminished mortality in patients hospitalized with COVID-19, that was significant for the FIASMA amlodipine [22]. Furthermore, data from the AP-HP Health Data Warehouse [23][24][25] showed that use of antidepressants, many of them being FIASMA, and the FIASMA hydroxyzine, were significantly associated with reduced mortality in patients hospitalized for COVID-19. Finally, results from a large US retrospective cohort study found that selective serotonin reuptake inhibitor (SSRI) antidepressants, and more specifically fluoxetine and fluoxetine or fluvoxamine, which are FIASMA, were significantly associated with reduced mortality [26].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…A multicentre observational retrospective cohort study was conducted at 36 Assistance publique-Hôpitaux de Paris (AP-HP) hospitals (Hoertel et al, 2021c(Hoertel et al, , 2021dSánchez-Rico et al, 2021). We included all adults aged 18 years or over who have been admitted to these medical centres from the beginning of the epidemic in France, i.e.…”
Section: Setting and Cohort Assemblymentioning
confidence: 99%
“…COVID-19 was ascertained by a positive reversetranscriptase-polymerase chain reaction (RT-PCR) test from analysis of nasopharyngeal or oropharyngeal swab specimens. This observational study using routinely collected data received approval from the Institutional Review Board of the AP-HP clinical data warehouse (decision CSE-20-20_COVID19, IRB00011591, 8 April 2020) and is part of a broader project aiming at examining the potential associations between psychotropic medications and COVID-19-related mortality, deposited in French at the 'Entrepôt de Données de Santé' (EDS) website (https://eds.aphp.fr/recherches-en-cours), which has led to several publications (Hoertel et al, 2021c(Hoertel et al, , 2021dSánchez-Rico et al, 2021). AP-HP clinical Data Warehouse initiatives ensure patient information and informed consent regarding the different approved studies through a transparency portal in accordance with European Regulation on data protection and authorisation no.…”
Section: Setting and Cohort Assemblymentioning
confidence: 99%